Association Between Exposure to Effervescent Paracetamol and Hospitalization for Acute Heart Failure: A Case‐Crossover Study. (19th February 2022) - Perrin, Germain; Arnoux, Armelle; Berdot, Sarah; Katsahian, Sandrine; Danchin, Nicolas; Sabatier, Brigitte
Abstract: We investigated whether effervescent paracetamol, as an important source of nondietary sodium and fluid load, is associated with a transient increase in the risk of hospitalization for acute heart failure (AHF). We conducted a unidirectional case‐crossover study using data from the 1 in 97th representative sample from the French health care database. Subjects aged ≥18 years, hospitalized for AHF during the 2014‐2016 period, were included. Exposure to effervescent paracetamol was compared between a risk period (ie, 15 days immediately before admission for AHF) and 3 earlier 15‐day control periods, to test a possible trigger effect of effervescent paracetamol intake on AHF. Adjusted odds ratios (aORs) were estimated with a conditional logistic regression. We identified 4301 patients hospitalized for AHF. We found that 5.7% of AHF subjects were exposed to effervescent paracetamol during the risk period, as compared with 4.1% during the control periods (aOR, 1.56 [95% confidence interval [CI], 1.27‐1.90]; P < .001). This association was also found in the subgroup of subjects with hypertension (aOR, 1.45 [95%CI, 1.13‐1.87]; P = .004, n = 2648) and in the subgroup of subjects aged ≥83 years (aOR, 1.70 [95%CI: 1.28‐2.24], P < .001, n = 2238). A similar analysis, considering exposure to noneffervescent paracetamol, did not support the existence of an indication bias likely to explain the association observed for effervescent paracetamol. This study suggests an association between effervescent paracetamol and admission for AHF and should be confirmed with other complementary study designs.